Rainier and Grace - Robinson, Jeffrey, 1945- (london Fontana Books, 1989)
The author has gained the co-operation of Prince Rainier III and his children as well as direct access to the royal archives for this account of the marriage of Prince Rainer and Princess Grace of Monaco. It includes anecdotes from such figures as Frank Sinatra, Winston Churchill, and King Farouk.
Include Notes and Index
Keywords: Monaco -- Families -- Princes